Investigating the Shear Characteristics of Geomembrane–Sand Interfaces Under Freezing Conditions - Dun Chen; Guoyu Li; Pengfei He; Hang Zhang; Jie Sheng; Miao Wang (Designs)
This study experimentally investigates the effects of freezing conditions on the shear characteristics of geomembrane–soil interfaces, employing a temperature-controlled direct shear apparatus. The findings reveal significant variations in shear stress–shear displacement patterns at the soil–geomembrane interface under different thermal conditions. At positive temperatures, the interface manifests strain hardening behavior, whereas at negative temperatures, it transitions from weak softening at low normal stress to strong strain softening at high normal stress. The shear displacement–normal displacement curves under varying temperature and normal stress conditions demonstrate dilatant behavior, with initial increases in normal displacement followed by a decrease as temperature drops. Notably, the interface friction angle is markedly higher at negative temperatures compared to positive, undergoing an initial increase, a period of stable development, and a subsequent rise with further temperature reduction. The average shear strength ratio at the interface is observed to be as low as 0.58 at 20 °C, approaches unity between −2 °C and −6 °C, and exhibits a significant increase at −10 °C. These findings are helpful for the application of geomembranes in frozen soil engineering.